Population genetic analyses unveiled genetic stratification and differential natural selection signatures across the G-gene of viral hemorrhagic septicemia virus - Nigar, Kiran; Kakakhel, Sehrish; Khan, Asifullah; Khan, Hizbullah; Zaib, Komal; Wen, Shaoqing (Frontiers in Genetics, 2022)
Viral Hemorrhagic Septicemia Virus (VHSV) is the most lethal pathogen in the aquaculture, infecting more than 140 fish species in marine, estuarine, and freshwater environments. VHSV is an enveloped RNA virus that belongs to the family Rhabdoviridae and the genus Novirhabdovirus. The current study is designed to infer the worldwide VHSV isolates genetic diversity and evolutionary dynamics based on G-gene sequences. The complete G-gene sequences of VHSV were retrieved from the public repositories with known timing and geography details. Pairwise statistical analysis was performed using ARLEQUIN. The Bayesian model-based approach implemented in the STRUCTURE software was used to investigate the population genetic structure and phylogenetic tree were constructed using Mega-X and IQ tree. The natural selection analysis was assessed using different statistical approaches, including IFel, MEME, and SLAC. The global VHSV samples are stratified into five genetically distinct subpopulations. The STRUCTURE analysis unveiled spatial clustering of genotype-Ia into two distinct clusters at K=3. However, at K=5 the genotype-Ia samples, deposited from Denmark, showed temporal distribution into two groups. The analyses unveiled that the genotype-Ia samples stratified into subpopulations possibly based on Spatio-temporal distribution. Several VHSV samples are characterized as genetically admixed or recombinant. Besides, differential or sub-population cluster-specific natural selection signatures were identified across the G-gene codon sites among the VHSV isolates. The evidence of low recombination events elucidates that genetic mutations and positive selection events have possibly driven the observed genetic stratification of VHSV samples.